Benign Paroxysmal Positional Vertigo Risk Factors Unique to Perimenopausal Women - Jeong, Seong-Hae (Frontiers in Neurology, 2020)
Many investigations have found an increased incidence of benign paroxysmal positional vertigo (BPPV) in women, and clinical experience with the elderly has shown that BPPV can develop due to increased hormonal fluctuations, especially during menopause. Therefore, knowledge about neurochemicals and their involvement with BPPV is imperative for the examination of neurological issues in women. This review will discuss appropriate gender-based considerations of BPPV based on experimental and clinical evidence. The literature describes 2 lines of evidence regarding the association of perimenopause in women and development of BPPV: (1) experimental evidence: the existence of estrogen receptors in the inner ear, otoconial malformations in osteopenic/osteoporotic rats, changes in otoconin 90 caused by hormone replacement therapy, and impaired calcium absorption following estrogen deprivation corrected by estrogen replacement therapy and (2) clinical evidence: epidemiological aspects, osteoporosis and estrogen deficiency. Future studies are necessary to validate the effects of hormonal replacement therapies and phytoestrogen in women with recurrent BPPV.